Pengaruh Struktur Modal dan Risiko Operasional terhadap Profitabilitas pada Industri Perbankan di Indonesia - Margaretha, Farah; Nurul, Istania (Business and Management Review, 2012)
The study’s purpose is to acknowledge the influence of capital structure and operational risk on profitability of banking industry in Indonesia. The samples are banking industries in Indonesian Stock Exchange for the period of 2004 up to 2009. Independent variables in this study included capital structure that measured by liability ratio and equity ratio, and operational risk that measured by portfolio concentration, whereas dependent variable is profitability that measured by profit margin. Beside that, control variabel is macroeconomics that measured by inflation rate. With using purposive sampling, the total of sample in this study is 22 companies of banking industries. Data analysis model are simple linear regression and t-test. Based on t-test, the result of capital structure that measured by both liability ratio and equity ratio has a significant impact to profitability, capital structure that measured by both liability ratio and equity ratio doesn’t has a significant impact to operational risk, and operational risk doesn’t has a significant impact to profitability. Meanwhile inflation rate doesn’t affect liability ratio, equity ratio, portfolio concentration, and profit margin, This result indicates that the company’s management has to consider capital structure, whereas can be influence the profitability. Keywords: capital structure, operatinal risk, profitability DAFTAR PUSTAKA Afza, T. & Nazir, M.S. (2009) Impact of Aggressive Working Capital Management Policy on Firms’ Profitability, Journal of Applied Finance, 15(8). Changchien, I.J. (2000). An exploration and empirical evidence for the influential factors of property-liability insurance industry’s capital structure, Insurance monograph, 62: 145-63. Chen, J.S., Chen, M.C. & Chen, T.H. (2009). Influence of Capital Structure and Operational Risk on Profitability of Life Insurance Industry in Taiwan, Journal of Modelling in Management, 4(1): 7-18. Chen, Y.C. & Tsai, C.H. (2000). Capital structure and risk in life company, Insurance Monograph, 18(1): 75-92.R Cummins, J.D. & Harrington, S.E. (1988). The Relationship between Risk and Return: Evidence for Property-Liability insurance stocks, Journal of Risk and Insurance, 55(1): 15-32. Cummins, J.D. & Sommer, D.W. (1996). Capital and Risk in Property-Liability insurance markets, Journal of Banking & Finance, 20: 1069-92. Gitman, Lawrence J. (2009). Principle of Management Finance, (11thEd.). Boston: Pearson Education, Inc. Jensen, M.C. & Meckling, W. (1976). Theory of the firm: managerial behavior, agency cost, and capital structure, Journal of Financial Economics, 3: 305-60. Lin, W.C. & Huang, H.M. (2002). Fair Surplus Value of the Property-Liability Insurer Under Catastrophe risk, Journal of Risk Management, 4(1): 1-18. Margaretha, Farah. (2005). Manajemen Keuangan Investasi dan Sumber Dana Jangka Panjang. Jakarta : Grasindo. Modigliani, F. & Miller, M.H. (1958). The Cost of Capital, Corporation Finance, and  The Theory of Investment, American Economic Review, 48: 261-97. Myers, S.C. & Majluf, N.S. (1984). Corporate Financing and Investment Decisions when Firms Have Information that Investors Do Not Have, Journal of Financial Economics, 13: 187-221. Staking, K.B. & Babbel, D.F. (1995). The Relation between Capital Structure, Interest rate Sensitivity, and Market value in the Property-liability Insurance Industry, Journal of Risk and Insurance, 62(4): 690-718.